The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/cmdc.200600133
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of Mixed MT1‐Agonist/MT2‐Antagonist Melatonin Receptor Ligands

Abstract: Herein we report attempts to optimize the pharmacological properties of 5-(2-hydroxyethoxy)-N-acetyltryptamine (5-HEAT), a melatonin receptor ligand previously described by us. Several 5-substituted and 2,5-disubstituted N-acyltryptamines were synthesized and evaluated in vitro for the human cloned MT(1) and MT(2) receptors. From this series of N-acyltryptamines the 2-bromo derivative (5 c) retains the interesting efficacy profile of 5-HEAT and shows increased melatonin receptor affinities; it represents one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…Several 5substituted and 2,5-disubstituted N-acyltryptamines were synthesized for this purpose. 1055 From this series of Nacyltryptamines, the 2-bromo derivative retains an interesting efficacy profile. For this experiment they used PTAB for the bromination of various substrates.…”
Section: -Bromo-55-dimethylhydantoinmentioning
confidence: 99%
See 1 more Smart Citation
“…Several 5substituted and 2,5-disubstituted N-acyltryptamines were synthesized for this purpose. 1055 From this series of Nacyltryptamines, the 2-bromo derivative retains an interesting efficacy profile. For this experiment they used PTAB for the bromination of various substrates.…”
Section: -Bromo-55-dimethylhydantoinmentioning
confidence: 99%
“…Spadoni et al reported attempts to optimize the pharmacological properties of 5-(2-hydroxyethoxy)- N -acetyltryptamine, a melatonin receptor ligand. Several 5-substituted and 2,5-disubstituted N -acyltryptamines were synthesized for this purpose . From this series of N -acyltryptamines, the 2-bromo derivative retains an interesting efficacy profile.…”
Section: Bromination Reactionsmentioning
confidence: 99%
“…Compounds with subnanomolar affinity and modest selectivity for the MT 1 subtype (MT 2 /MT 1 selectivity ratios approximately ranging from 20 to 40) have been obtained when a 4‐phenylbutyl group was introduced at the C2‐position of the bicyclic scaffold, as exemplified by compounds 29 [117], 30 [118] and 31 [119] in Figure 3. By replacement of the methoxy group of MLT with a 5‐hydroxyethoxy substituent interesting compounds were obtained, some of which ( 32 [120], 33 [121]) have similar binding affinity for the two receptor subtypes, but functional selectivity on GTPγS binding, as they displayed MT 1 agonist and MT 2 antagonist properties. Taken together, all these results have led to the hypothesis that MT 1 selectivity is favored by replacement of the 5‐methoxy group by a larger substituent.…”
Section: Melatonin Receptor Selective Agonistsmentioning
confidence: 99%
“…In order to minimize the number of reaction steps and to achieve the best possible overall yield, we have chosen a one-pot Ra-Ni hydrogenation/acetylation procedure previously reported for the reduction of nitriles to give directly the N-acetylated product. 11 We were pleased to find that aldoxime 8 could be converted into agomelatine using Ra-Ni hydrogenation in the presence of acetic anhydride in an excellent 98% yield.…”
Section: Figure 1 Chemical Structures Of Melatonin and Agomelatinementioning
confidence: 99%